Determination of the parameters for a hypoplastic constitutive model on clay to be used in the finite element method Tochnog - Hernández-Villegas, Sofía (2018)
A constitutive model attempts to model the behavior of the soil. Nowadays, there are great variety of methods, one of the most well-known constitutive models is the one of Mohr Coulomb, however it doesn’t take into account the nonlinear behavior of the soil, an hypoplastic model does, which it’s very important in the actual practice of engineering. The hypoplasticity is a framework that was at first developed for granular materials, but given the advantages of using such a model, Masín [2] proposed to use such model for clays, that sometimes are used in earth dams which are of great importance and such a model could allow a better understanding and modelling since it takes into account the nonlinear and hysteretic behavior. The following investigation has as an objective to explain the procedure for the determination of the parameters needed in order to developed and hypoplastic model according to Masín [2] by using the kaolin clay, by means of laboratory tests, as the direct shear box, consolidation or oedometer and basic index test. With the obtained results, it can be seen that the parameters to use can easily be determine by simple laboratory tests, so in conclusion it can be observed that it is a feasible method to put in practice at the same time that that is able to reproduce efficiently the cyclic behavior of soils from small deformations to failure and which can be implemented in numerical dynamic calculations with the use of a finite element software.